2022
DOI: 10.1155/2022/1565094
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Role and Mechanism of ZEB1 in Regulating Cervical Carcinoma Progression via Modulating PD-1/PD-L1 Checkpoint

Abstract: Background. Cervical carcinoma (CC) is a common and highly malignant tumor in women. The involvement of zinc finger E-box binding homeobox 1 (ZEB1) in many kinds of tumors has been well-documented; however, its role and mechanism in CC remain to be clarified. Objective. This study investigated the mechanism of ZEB1 in modulating the growth and metastasis of CC cells. Methods. The expression of ZEB1 in CC tissues and adjacent normal counterparts was determined by reverse transcription-polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…ZEB1 functions to regulate important transcriptional networks necessary for cell differentiation, maintenance, and function [ 67 ]. It can modulate the PD-1/PD-L1 checkpoint [ 68 , 69 ], promote cell proliferation and migration, and inhibit apoptosis [ 70 ]. It also plays a crucial role in the maintenance of cancer stem cells [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZEB1 functions to regulate important transcriptional networks necessary for cell differentiation, maintenance, and function [ 67 ]. It can modulate the PD-1/PD-L1 checkpoint [ 68 , 69 ], promote cell proliferation and migration, and inhibit apoptosis [ 70 ]. It also plays a crucial role in the maintenance of cancer stem cells [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…These targeted proteins and genes play critical roles in cell proliferation, apoptosis, motility, angiogenesis, invasion, and metastasis in thyroid cancer. For example, AKT is vital in the PI3K/Akt signaling pathway [49], ZEB1 modulates the PD-1/PD-L1 checkpoint and cancer stem cell maintenance [50][51][52], ZEB2 triggers epithelial-mesenchymal transition and activates the Wnt/betacatenin pathway [53,54], RAB5C regulates angiogenesis and cell migration [55][56][57], and DUSP6 is involved in thyroid tumorigenesis by regulating the ERK1/2 pathway [58]. Three ncRNAs-TUG1, n384546, and circNUP214-can sponge and suppress miR-145, leading to cancer progression and metastasis [10,11,59].…”
Section: Functional Analysis Of Mmp9 and Mir-145mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%